Fatal Acanthamoeba Encephalitis in a Patient With a Total Artificial Heart (Syncardia) Device - Tan, Susanna K. (Open Forum Infect Dis, 2014)
Acanthamoeba encephalitis is an uncommon but often fatal infection complication. Here we report the first case of Acanthamoeba encephalitis in a patient with a Total Artificial Heart device.